Proyecciones para el mejoramiento de la calidad de los servicios turísticos en la ciudad de Quevedo, año 2019 - Cornejo Cruz, Stalin Frixon (2020)
Tourism makes an important contribution to the economies of developing countries, growth in the sector has been faster in underdeveloped than in developed countries, so in some of them it is the first income of its economy In Ecuador the activity Tourism has had significant growth in recent decades, natural attractions are the most representative to attract tourists worldwide. The tourist of the new millennium does not simply look for with the passive complementation of the tourist attractions or with the enjoyment of the sun / beach binomial, it also seeks new motivations oriented to the valuation of the environmental aspects and cultural authenticity of the destination. Considering that tourism represents one of the main items of economic income worldwide, we can affirm that Ecuador cannot be the exception, since it is a country that has a great natural wealth, the diversity of its four regions has given rise to thousands of species of flora and fauna. Not surprisingly, Ecuador is considered one of the 17 countries where the greatest diversity of the planet is concentrated. It also has a wide range of cultures in its three continental regions (coast, mountains and east) where 13 indigenous nationalities coexist, who have their own worldview of the world.